Description of the first species of the genus Archaeopodagrion (Philogeniidae: Odonata) from the Colombian Central Andes - Bota-Sierra, Cornelio A. (Zootaxa, 2025)
Archaeopodagrion oelmannae sp. nov. is described from the northern Central Colombian Andes, representing the first record of the genus in the Central Cordillera. The species seems to be very rare, only one male specimen found after an extensive sampling effort. The species is probably endangered, as it has been found only in a small protected forest in a region where the habitat is threatened by agricultural expansion. This paper also presents a novel taxonomic key for the genus based on the prothorax of the males and a distribution map for all species in the genus.